Recurrent NEDD4L Variant in Periventricular Nodular Heterotopia, Polymicrogyria and Syndactyly - Stouffs, Katrien; Verloo, Patrick; Brock, Stefanie; Régal, Luc; Beysen, Diane; Ceulemans, Berten; Jansen, Anna C.; Meuwissen, Marije E.C. (Frontiers in Genetics, 2020)
NEDD4L encodes a ubiquitin ligase which is expressed in the cortex and ventricular zone of the fetal brain. Missense variants in NEDD4L have been reported in nine patients with periventricular nodular heterotopia (PNH), polymicrogyria, cleft palate and syndactyly. All reported variants are located in the HECT domain, causing deregulation of signaling pathways, including the AKT/mTOR pathway. Here we describe a first familial case with four affected members with a high degree of intra-familial phenotypic variability. Phenotypic features in the proband consisted of severe neurodevelopmental delay, refractory seizures, bilateral PNH and perisylvian polymicrogyria. The other family members were less severely affected with mild developmental delay and isolated bilateral PNH. All family members had syndactyly. An unrelated patient presented with severe neurodevelopmental delay, seizures and hypospadias, expanding the phenotypic spectrum. MRI revealed bilateral PNH and perisylvian polymicrogyria. All tested patients carry the recurrent variant c.623G>A, p.(Arg208Gln) in the WW domain of NEDD4L. The variant in the unrelated patient occurred de novo. This is the first report of a NEDD4L variant located in the WW domain which is probably involved in the recognition of substrates for ligation suggesting a loss of function variant.